2009
DOI: 10.1038/ijo.2009.155
|View full text |Cite
|
Sign up to set email alerts
|

Satiety and amino-acid profile in overweight women after a new treatment using a natural plant extract sublingual spray formulation

Abstract: Objective: To test the effect on satiety of a formulation comprising plant extracts naturally containing 5-hydroxytryptophan, delivered as sublingual spray (5HTP-Nat Exts), administered five times a day for 2 months. Design: Two-month, randomized, double-blind, placebo-controlled trial. Subjects: A total of 27 healthy, adult overweight women were randomly assigned to the treatment (14) or the placebo group (13). Measurements: Visual analog scales were used to assess appetite sensations every day. Moreover, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
0
11
0
2
Order By: Relevance
“…All 24-h dietary recalls were completed (one weekday and one weekend day) at baseline and at the 4, 8 and 12 weeks' time points (39) . Participants were asked to recall the foods consumed over the previous 24 h. A 24-h period was defined as the time between when the participants woke up the previous day until the time they woke up the day of the interview (40) .…”
Section: Dietary Intake and Physical Activity Assessmentmentioning
confidence: 99%
“…All 24-h dietary recalls were completed (one weekday and one weekend day) at baseline and at the 4, 8 and 12 weeks' time points (39) . Participants were asked to recall the foods consumed over the previous 24 h. A 24-h period was defined as the time between when the participants woke up the previous day until the time they woke up the day of the interview (40) .…”
Section: Dietary Intake and Physical Activity Assessmentmentioning
confidence: 99%
“…Besides, a significant decrease in appetite and increase in hunger was seen by P. vulgaris (with dose of 100 mg/day; Spadafranca et al, ), C. fimbriata (with dose of 1,000 mg/day; Kuriyan et al, ), spinach (with dose of 5,000 mg/day; Rebello et al, , Stenblom, Egecioglu, Landin‐olsson, & Erlanson‐albertsson, ), flaxseed (with dose of 2,500 mg/day; Ibrugger, Kristensen, Mikkelsen, & Astrup, ), fenugreek (with dose of 8,000 mg/day; Mathern, Raatz, Thomas, & Slavin, ), G. cambogia (with dose of 1,000 mg/day; Mayer et al, , Preuss et al, ), green coffee (Roshan, Nikpayam, Sedaghat, & Sohrab, ), and the combination simplicifolia , asiatica , Taraxacum officinale , Cynara Scolymus , Paullina Sorbilis , Alga Klamath (Rondanelli, Klersy, Iadarola, Monteferrario, & Opizzi, ), and a combination of G. cambogia and Amorphophallus konjac (Vasques et al, ; Figure ). Some other articles have shown that Gundelia tournefortii (Hajizadeh‐Sharafabad, Alizadeh, Mohammadzadeh, Alizadeh‐Salteh, & Kheirouri, ), Coleus forskohlii (Loftus et al, ), N. sativa (Mahdavi et al, ), Garcinia atroviridis (Roongpisuthipong, Kantawan, & Roongpisuthipong, ), C. fimbriata (Kuriyan et al, ), a combination of ephedra and caffeine (Hackman et al, ) as well as a combination of walnut and flaxseed (Wu et al, ) significantly reduces energy intake (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Aufbauend auf einer randomisierten, doppelblinden, placebokontrollierten Pi lotstudie (29) wurde eine ebensolche Stu die mit 20 übergewichtigen Frauen durch geführt. Die Probandinnen wurden ange wiesen, zu den persönlich abgestimmten,…”
Section: Adipositasunclassified